1982
DOI: 10.1016/0035-9203(82)90146-8
|View full text |Cite
|
Sign up to set email alerts
|

Crithidia fasciculata: a catalase-containing trypanosomatid sensitive to nitroheterocyclic drugs

Abstract: Crithidia fasciculata, which contains high levels of a cytosolic catalase, is sensitive to inhibition by at least two nitroheterocyclic drugs, Nifurtimox and MK 436, both of which are also active against Trypanosoma cruzi. Drug sensitivity is not enhanced in organisms containing reduced levels of catalase. The ultrastructural lesions in T. cruzi produced by nitroheterocycles, especially the swelling and gross vacuolation of the mitochondria, are seen also in C. fasciculata. These results are not consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Heme can possibly be stored in catalase and used under the heme‐limited conditions. It has been shown that after 2 days of heme starvation, only 6% of the catalase activity in C. fasciculata was retained, whereas the oxygen consumption and cytochrome‐mediated respiration remained unaffected . In T. brucei , we recapitulated (to some extent) the phenotype observed in T. cruzi after the expression of a bacterial catalase in vitro .…”
Section: Discussionmentioning
confidence: 76%
“…Heme can possibly be stored in catalase and used under the heme‐limited conditions. It has been shown that after 2 days of heme starvation, only 6% of the catalase activity in C. fasciculata was retained, whereas the oxygen consumption and cytochrome‐mediated respiration remained unaffected . In T. brucei , we recapitulated (to some extent) the phenotype observed in T. cruzi after the expression of a bacterial catalase in vitro .…”
Section: Discussionmentioning
confidence: 76%
“…One study with C. fasciculate, showed that organisms with low levels of the enzyme trypanosomatid catalase maintain their sensitivity to nifurtimox (2). These results contradict the hypothesis that the action of nifurtimox (2) involves the accumulation of hydrogen peroxide due to the absence of catalase (Gutteridge et al, 1982). Moreover, recently, five peroxidases were identified in T. cruzi: two tryparedoxin peroxidases (Wilkinson et al, 2000;Piacenza et al, 2008;Trujillo et al, 2004), two glutathione-dependent peroxidases (Wilkinson et al 2002a;Wilkinson et al, 2002b), and one ascorbate-dependent heme peroxidase (Wilkinson et al, 2002c) showing, in contrast to previous studies that the parasite has a complex and effective system to deal with oxidative stress.…”
Section: Nifurtimox and Benznidazolementioning
confidence: 73%
“…Activity of ACOXs and other H 2 O 2 -producing enzymes such as d -amino acid oxidase and 2-hydroxy acid oxidase could not be detected in T. brucei , nor have these enzymes been detected in any of the more recent glycosomal proteome analyses. However, the latter two oxidases and catalase have been reported for other trypanosomatids like C. fasciculata , but not in association with the organelles ( Opperdoes et al, 1977 ; Gutteridge et al, 1982 ; Opperdoes, 1987 ). We detected in TriTrypDB an A. deanei oxidase with a FAD-binding domain and PTS1, annotated as having a predicted 2-hydroxy acid oxidase function ( Supplementary Table S2 ).…”
Section: Introductionmentioning
confidence: 88%